PENDEKATAN HERMENEUTIK NASR HAMID ABU ZAYD DALAM STUDI AL-QUR'AN: ANALISIS TERHADAP KONSEP TEKS DAN PRODUK BUDAYA - Iwan Setiawan; Abd Aziz (LP2M Universitas PTIQ Jakarta, 2025)
This study examines Nasr Hamid Abu Zayd’s hermeneutical approach to the Quran, focusing on his concept of the Quran as a